Postactivation potentiation effect of overloaded cycling on subsequent cycling Wingate performance. - Doma, K.; Leicht, A. S.; Schumann, M.; Nagata, A.; Senzaki, K.; Woods, C. E. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: This study examined the postactivation potentiation effects of overloaded cycling on subsequent Wingate performance. METHODS: Twenty anaerobic-trained men took part in this study. The participants were randomly allocated to complete three testing sessions separated by 7 days. Each week, participants either undertook a control session (CON) consisting of a sub-maximal cycling warm-up protocol followed by a Wingate Test, or separate sessions involving an overloaded 10-second cycling PAP protocol followed by a Wingate Test at 5 (T5) or 10 (T10) minutes, post-PAP protocol. Power outputs, cadence, total work, fatigue rate, heart rate and capillary lactate measures were recorded from each Wingate Test. Measures were compared between these sessions and between sessions that generated the greatest peak power output (Bestpeak-P) and mean power output (Bestmean-P) via repeated measures ANOVA with effect sizes (ES) also calculated. RESULTS: A significantly greater mean power output, total work and lactate levels were exhibited during the T10 condition compared to the CON condition (P<0.05, ES=1.57). Whilst not significant (P=0.06), a greater peak power output was exhibited during the Bestpeak-P condition compared to the CON condition with a large effect (ES=0.95). CONCLUSIONS: Results indicated that an overloaded cycling protocol increased power output and lactate measures in anaerobic-trained men during a 30-second, Wingate Test. Overloaded cycling enhances subsequent anaerobic performance and is therefore likely to provide greater training stimuli for anaerobically trained individuals.